Assessing the level of knowledge and attitudes of young people about nutrition and oral health: Nutrition and oral health - Saveanu, Catalina; Cretu , Cosmin Constantin; Anistoroaei, Daniela; Saveanu, Alexandra Ecaterina; Golovcencu , Loredana (Progress in Nutrition, 2022)
Oral health is an important component of general health that directly influences the quality of life. The purpose of this study was to assess the level of knowledge and attitudes regarding the interrelationship between diet and oral health, the testable hypothesis being that there are differences between the level of knowledge of food hygiene in the study group. Material and method: The study included 718 Romanian subjects, aged between 12-18 years old, randomly selected. The data were selected by the questionnaire method and collected using a link and were introduced into a database used SPSS 26.00 for Windows. Were applied 16 questions about the knowledge and attitudes regarding the diet. Results: About 20% of the subjects do not know that there is a link between food and oral diseases, p≤0.05 and about a third do not know the connection between the consumption and frequency of consumption of carbonated drinks and the pathology of the oral cavity. Smoking is considered a harmful activity for the oral cavity for 79.1% (568) of the subjects, alcohol for 52.1% (374) and drugs by 49.7% (357) with p≤0.05. Conclusion: There are differences between the level of knowledge about diet in the studied group, according to sex and level of education, the subjects require a sustained and targeted education on important aspects that influence the quality of oral health.